Multivariate Pattern Analysis of the Neural Correlates of Smoking Cue Attentional Bias - Elton, Amanda (Pharmacol Biochem Behav, 2019)
The automatic capture of attention by drug cues, or attentional bias, is associated with craving and predicts future drug use. Despite its clinical significance, the neural bases of attentional bias to drug cues is not well understood. To address this gap, we undertook a neuroimaging investigation of the neural correlates of attentional bias towards smoking cues. Twenty-nine adults, including 14 active smokers and 15 non-smokers, completed a spatial cuing task during fMRI. A multivariate pattern analysis (MVPA) decoded the neural responses to the brief presentation of smoking versus neutral images. These data were correlated with behavioral measures of attentional bias, which included analyses targeting the neural correlates of response facilitation and cue-related task interference. We detected a set of brain-behavioral correlates that were similar across both smokers and non-smokers, indicating a role for stimuli salience in the absence of nicotine conditioning in smoking cue attentional bias. However, multiple smoking-related modifications to the neural correlates of attentional bias and its components were also identified. For example, regions demonstrating smoking-related differences in the neural correlates of attentional bias included the rostral anterior cingulate cortex and inferior frontal gyrus. Response facilitation effects of smoking were observed in the right orbitofrontal gyrus and bilateral middle temporal gyrus. Smoking-cue related task interference was related to smoking-related effects in the frontal eye fields. Our findings suggest that multiple cognitive, affective, and visual object recognition processes contribute to attentional bias towards smoking cues, and suggest multiple circuit modifications that may contribute to perpetuation of addiction.